2022
DOI: 10.3389/fphar.2022.944886
|View full text |Cite
|
Sign up to set email alerts
|

Empagliflozin activates Sestrin2-mediated AMPK/mTOR pathway and ameliorates lipid accumulation in obesity-related nonalcoholic fatty liver disease

Abstract: Empagliflozin (EMPA) therapy has led to improvements in patients with non-alcoholic fatty liver disease (NAFLD). Sestrin2 is a stress-inducible protein that controls the AMPK-mTOR pathway and inhibits oxidative damage in cells. This study investigated the functional implications of EMPA on the multifactorial pathogenesis of NAFLD and potential underlying molecular mechanisms of pathogenesis. An in vitro model of NAFLD was established by treating HepG2 cells with palmitic acid (PA); an in vivo model of NAFLD wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 47 publications
0
5
0
Order By: Relevance
“…Such as, PA-treated HK-2 renal tubular cells were used for in vitro assessments of obesity-induced nephropathy [ 39 ]. The in vitro model of non-alcoholic fatty liver disease was established by treating HepG2 cells with PA [ 40 ]. Moreover, PA-induced osteoarthritis cell models was well used to study obesity-related OA [ 41 , 42 ], hence, we used PA treated chondrocyte cell model for further studies.…”
Section: Discussionmentioning
confidence: 99%
“…Such as, PA-treated HK-2 renal tubular cells were used for in vitro assessments of obesity-induced nephropathy [ 39 ]. The in vitro model of non-alcoholic fatty liver disease was established by treating HepG2 cells with PA [ 40 ]. Moreover, PA-induced osteoarthritis cell models was well used to study obesity-related OA [ 41 , 42 ], hence, we used PA treated chondrocyte cell model for further studies.…”
Section: Discussionmentioning
confidence: 99%
“…While empagliflozin's primary mechanism of action is through the inhibition of SGLT2 in the kidney, it has also been shown to affect intracellular signaling pathways in various cell types. For instance, empagliflozin has been reported to activate adenosine monophosphate-activated protein kinase (AMPK) in the liver ameliorating lipid accumulation in obesity-related nonalcoholic fatty liver disease [ 54 ] and in skeletal muscle promoting fat utilization and hence presumably contributing to improved insulin sensitivity [ 55 , 56 ]. Additionally, empagliflozin-activation of AMPK in cardiomyocytes has been shown to reduce lipopolysaccharide (LPS)-induced inflammatory response and counteract LPS-impaired cellular ATP/ADP ratio, suggesting potential mechanisms for cardioprotection.…”
Section: Discussionmentioning
confidence: 99%
“…Among proteins involved in the development of liver tissue cellular defense against oxidative stress, oxidative DNA damage, inflammation, and steatohepatitis, peroxiredoxins 1 (Prx1) and 6 (Prdx6) and sestrin 2 (SESN2) were considered promising potential diagnostic biomarkers for the early stage of NAFLD/NASH, which may also influence the mTOR [ 27 , 28 ] ( Table 1 and Table 2 ). Prdx1 and Prdx6 are involved in Akt/mTOR, AMPK/mTOR, PI3K/Akt, FoxO and p53 signaling pathways, and ubiquitin-mediated proteolysis [ 59 , 60 ].…”
Section: Signaling and Metabolic Pathways In The Regulation Of Nafld/...mentioning
confidence: 99%
“…Prdx1 and Prdx6 are involved in Akt/mTOR, AMPK/mTOR, PI3K/Akt, FoxO and p53 signaling pathways, and ubiquitin-mediated proteolysis [ 59 , 60 ]. It was also demonstrated that protein levels of SESN2 were positively correlated with AMPK/mTOR pathway components and induced expression of lipogenesis-related genes in NAFLD model HFD-fed C57BL/6 mice liver and palmitic acid (PA)-stimulated HepG2 cells [ 28 ].…”
Section: Signaling and Metabolic Pathways In The Regulation Of Nafld/...mentioning
confidence: 99%